Perspectives of the Ideal Assisted Living Facilities from Depression Era Nurses - Jason Bischoff; Kelly Timmer; Cindy Walton; Connie White; Karen Zulkowski (Online Journal of Rural Nursing and Health Care, 2017)
The diversity of the elderly combined with a prolonged life span means their response to changing care and health is varied.  Today’s elderly population prefers to stay in their own homes.  However, as their health declines they become more dependent.  Their choice of housing is influenced by age, need for assistance, availability of their children, health care providers, services and facilities.  One type of housing choice that has recently become popular for elderly persons is assisted living facilities.  Little is known about how the rural elderly view what is important in an assisted living setting.  The purpose of this qualitative study was to determine qualities of a senior living facility that retired rural elderly nurses would include in their vision of the optimal assisted living accommodations.  Common themes that emerged were social environment, health and health care, diet and nutrition, exercise and recreation, social systems, and physical environment.